The Emerging Roles of CCN3 Protein in Immune-Related Diseases - Linan Peng; Yingying Wei; Yijia Shao; Yi Li; Na Liu; Lihua Duan (Mediators of Inflammation)
The CCN proteins are a family of extracellular matrix- (ECM-) associated proteins which currently consist of six secreted proteins (CCN1-6). CCN3 protein, also known as nephroblastoma overexpressed protein (NOV), is a member of the CCN family with multiple biological functions, implicated in major cellular processes such as cell growth, migration, and differentiation. Recently, CCN3 has emerged as a critical regulator in a variety of diseases, including immune-related diseases, including rheumatology arthritis, osteoarthritis, and systemic sclerosis. In this review, we will briefly introduce the structure and function of the CCN3 protein and summarize the roles of CCN3 in immune-related diseases, which is essential to understand the functions of the CCN3 in immune-related diseases.